Spatial patterns of zooplanktivore Chirostoma species (Atherinopsidae) during water-level fluctuation in the shallow tropical Lake Chapala, Mexico: seasonal and interannual analysis - Moncayo-Estrada,Rodrigo (2011)
This study addresses the influence of water-level fluctuations on fish distribution at two temporal scales: seasonal (dry and rainy) and interannual (low and high volume conditions). The analysis of abundance relationships among three zooplanktivore Chirostoma species at fifteen sites in Lake Chapala, Mexico, revealed the significant influence of contrasting conditions (P=0.0002). Seasonally, segregation was more related to species dominance in the dry season and exclusively related to environmental characteristics in the rainy season. Interanually, biotic influence occurred in the shallowest and the deepest episodes of the lake. Environmental characteristics influenced species distribution when the lake reached 25% of its volume. Site, depth, temperature, and salinity were the leading factors influencing fish distribution. These results emphasize the necessity to implement different management strategies according to lake volume, particularly when a critical threshold is reached.